The fusion characteristics of ashes from anthracite and biomass blends. Issue 5 (October 2018) - Lu, Guangjun; Zhang, Kai; Cheng, Fangqin
Abstract: Fusion characteristics of ashes from anthracite and biomass (pine sawdust and corn stalk) blends were investigated. These ashes were prepared in a muffle furnace (MF) and a drop tube furnace (DTF) at the temperatures of 815 °C and 1200 °C respectively. The fusion temperatures of ashes were measured in an ash fusion temperature analyzer, the morphological characteristics and element component of ashes were analyzed by means of SEM (Scanning Electron Microscope) fitted with EDS (Energy Disperse Spectroscopy). The minerals species and transformation characteristics were also detected using XRD (X-ray diffraction). The fusion temperatures of MF blends ashes were lower than those of DTF blends ashes because of the difference of ash preparation temperatures. The structures of ashes made in MF were dispersed and loose, but the ashes made in DTF were denser and larger resulting in obvious agglomeration. The fusion temperatures decreased with biomass addition ratio increasing due to large amounts of alkali and alkali-earth species in pine sawdust/corn stalk ash regardless the ash preparation method. K and Ca-bearing compounds can react with aluminosilicates in anthracite to create low temperature eutectics which can decrease the fusion temperatures of anthracite and biomass blends. Highlights: The fusion characteristics of ashes from combustion of anthracite blending biomass were studied. A muffle furnace (MF) and a drop tube furnace (DTF) were used to prepare ash samples. The fusion temperatures of the MF blends ashes were slightly lower than those of the DTF blends ashes. Biomass addition reduced the fusion temperatures of ashes.